Earnings Management, Equity-based Compensation, Economic Conjuncture and Governance Mechanisms: A Comparative Study between France and the United States - Bouras, Mehdi; Gallali, Mohamed Imen (International Journal of Economics and Financial Issues, 2017)
Based on a sample of 159 French firms and 203 U.S. firms for the period extending from 2003 to 2010, generally, we find that for both cases, managers engage in earnings’ management when they have a high percentage of equity-based compensation. The financial crisis was obviously important on managerial behavior and particularly on earnings management. Thus, the economic conjuncture is a new research question for equity compensation when it grants policy and earnings management. In addition, the governance mechanisms used to limit the opportunistic behavior of the manager also comes into play. Then we examine the governance mechanisms which encourage earnings management, particularly during allocation of equity compensation, where these two ideas have not been previously analyzed. We show that in contrast to a period of instability and economic recession, the manager has an incentive to earnings management to maximize his equity-based compensation during the period of economic growth. On the second point of research, we find on the one hand, that a governance mechanism which is effective in controlling earnings management that does not yield this result persists when awarding equity compensation. On the other hand, in the American case, the characteristics of the board of directors, and principally the compensation committee, and the ownership structure in the French case, can limit the opportunistic behavior of the manager during the allocation period of equity-based compensation. Keywords: Equity Compensation, Earnings Management, Economic Conjuncture, Governance Mechanisms JEL Classification: G35